DINAMIKA KISAH “SI KENCUR” DALAM MEMPERBAIKI SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS RETRIBUSI PELAYANAN PASAR: SUATU KAJIAN DRAMATURGI - Andry Yunanto; Ali Djamhuri; Yeney Widya Prihatiningtias (Universitas Negeri Malang, 2017)
This study aims to explore the role of actors in a story in improving the accounting information system in cash revenue of market retribution. The dynamics of the story tell about the story of the main character,